Sad, bad and mad : exploring child abandonment in South Africa. - Blackie, Deirdre Elizabeth (My University, 2015)
The following dissertation explores the experience and representations of child abandonment in urban Johannesburg, South Africa. I examine this complex social behaviour through a number of perspectives specifically: how it is portrayed in the media; how it is represented and managed by child protection officers; the lived experience of the abandoning mother and the abandoned child; and finally how it is understood in the context of Western biomedical principles and those of indigenous African ancestral beliefs. I suggest that child abandonment has been individualised and medicalised in South Africa. Individualised, in that it has been termed a problem that falls entirely within the domain of poor women, and frequently that these women are young teenagers. Medicalised in that a social behaviour that is not new, is increasingly being defined in medical terms through the portrayal and labelling of the abandoning mother as emotionally unstable and criminally insane. I argue that this has been done in an attempt to motivate for stricter surveillance and control over women’s sexual reproductive health and to divert attention from the state’s role in addressing this growing social challenge.
Keywords: Child abandonment; South Africa